A Digital Technique to Fabricate Segmental Individual Tooth Trays for Making an Impression of Multiple Crown Preparations. Issue 2 (19th November 2021) - Xu, Xiaoxiang; Xie, Qiufei; Zhang, Lei; Zhao, Yijiao; Cao, Ye
Abstract: A digital technique is described for designing and fabricating segmental individual tooth trays that can be used to make an impression of multiple preparations with high accuracy and efficiency. A digital model of prepared dentition was acquired. The segmental individual tooth trays with retention attachments and tissue stops were designed and 3D printed with light‐polymerizing resin. The segmental impression of each section of the prepared dentition was made with the corresponding individual tooth tray loaded with the impression material. A final overall impression was made to pick up the segmental individual tooth trays with a full arch tray.